The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0111639
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Myeloid Differentiation Primary Response 88 and Toll-Like Receptor 4 in Breast Cancer Patients

Abstract: PurposeBreast cancer remains a major cause of death in women worldwide, and tumor metastasis is the leading cause of death in breast cancer patients after conventional treatment. Chronic inflammation is often related to the occurrence and growth of various malignancies. This study evaluated the prognosis of breast cancer patients based on contributors to the innate immune response: myeloid differentiation primary response 88 (MyD88) and Toll-like receptor 4 (TLR4).MethodsWe analyzed data from 205 breast invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…The expression of MTDH are presented at a higher levels in TLR4 positive breast cancer cells (MDA-MB-231,MCF-7,and MDA-MB-468) than that in TLR4 negative T47D cell lines after treated with LPS, suggesting the pro-tumor role of TLR4 expressed on tumor cells [ 92 ]. Furthermore, TLR4 has also been reported correlation with metastasis of breast cancer cells [ 93 , 94 ] and has down favor on poor survival of breast cancer patients [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MTDH are presented at a higher levels in TLR4 positive breast cancer cells (MDA-MB-231,MCF-7,and MDA-MB-468) than that in TLR4 negative T47D cell lines after treated with LPS, suggesting the pro-tumor role of TLR4 expressed on tumor cells [ 92 ]. Furthermore, TLR4 has also been reported correlation with metastasis of breast cancer cells [ 93 , 94 ] and has down favor on poor survival of breast cancer patients [ 95 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, breast cancer remains a major cause of female deaths ( 9 ). Breast cancer can be broadly classified into four major molecular subtypes, depending on the specific genetic profile (i.e., luminal A, luminal B, triple-negative/basal-like and HER2 status) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a model of diethylnitrosamine-induced HCC in wild-type and TLR4-deficient mice, TLR4 stimulation of resident liver cells by intestinal microbiota was required for promoting HCC (Dapito et al, 2012). Finally, several studies demonstrated TLR4 overexpression by tumor cells associated with poor clinical outcome in breast cancer Ma et al, 2014), colorectal cancer (Cammarota et al, 2010) and pancreatic ductal adenocarcinoma (Zhang et al, 2010).…”
Section: Pro-tumoral Effects Of Tlr4mentioning
confidence: 99%